Customer Perceptions of Digital Banking Service Quality Amid Technological Transformation - Sri Wahyuni, Mirra; Herfianti, Meiffa; Selviani, Ayudho (Universitas Muhammadiyah Bengkulu, 2025)
This study analyzes customer perceptions of digital banking service quality in the era of rapid technological transformation. A qualitative phenomenological approach was employed, involving in-depth interviews with 18 customers and focus group discussions in Jakarta and Surabaya. Results indicate that transaction security is the dominant satisfaction factor (89% of respondents), followed by application usability (68% among younger users) and customer service responsiveness (72% reported complaints). Additional insights reveal expectations for fintech integration and personalized features. The study offers practical recommendations: improving interface design, bolstering digital security, optimizing technology-driven customer service, educating less tech-savvy customers, and enhancing regulatory oversight